ORTHOPTERAN DIVERSITY IN TROPICAL ECOSYSTEMS OF CENTRAL KERALA, INDIA - Rose Mathew, Leema; K. Joseph, Gigi; Elizabeth Cyril, Aleena (Indonesian Journal of Forestry Research, 2022)
Orthoptera is a diverse arthropod taxon that includes locusts, grouse locusts, short-horned grasshoppers, long-horned grasshoppers, katydids, crickets and mole crickets. They play crucial roles in food chains, nutrient cycling and pollination. The diversity of orthopterans in agroecosystems and grasslands located in the highlands and lowlands of Central Kerala were studied from December 2019 toMarch 2020. The study was conducted in Avoly of Ernakulam District and Venmony of Idukki District in Kerala by employing random sampling in 10 x10 m quadrats. A total of 35 species of orthopterans, belonging to two suborders, 10 families, 20 subfamilies, and 33 genera were recorded. Family Acrididae with fourteen species was the most dominant family followed by Tettigoniidae. Two species namely, Chitaura indica and Burrinia burri are endemic to the state of Kerala. It was found that the ranges of most of the orthopteran genera reported in our study extend all over the South East Asian countries. The highest number of Orthoptera was reported in December in both locations and it decreased towards March. Simpson’s diversity index value shows that both regions harbour a highly diverse orthopteran community. The diversity index value of Venmony is comparatively higher which might be due to the proximity of the study site to the natural forest ecosystem and fewer disturbances. More studies on the orthopteran fauna of Kerala are recommended which would help control their pest status and exploit their economic potential as food in animal husbandry.